Allelic functional variation of FimH among Salmonella enterica subspecies - Xiamei Kang; Jiaqi Chen; Xiao Zhou; Abdelaziz Ed-Dra; Min Yue (BMC, 2023)
Abstract Salmonella enterica has a wide diversity, with numerous serovars belonging to six different subspecies with dynamic animal-host tropism. The FimH protein is the adhesin mediating binding to various cells, and slight amino acid discrepancy significantly affects the adherence capacities. To date, the general function of FimH variability across different subspecies of Salmonella enterica has not been addressed. To investigate the biological functions of FimH among the six Salmonella enterica subspecies, the present study performed several assays to determine biofilm formation, Caenorhabditis elegans killing, and intestinal porcine enterocyte cell IPEC-J2 adhesion by using various FimH allele mutants. In general, allelic mutations in both the lectin and pilin domains of FimH could cause changes in binding affinity, such as the N79S mutation. We also observed that the N79S variation in Salmonella Dublin increased the adhesive ability of IPEC-J2 cells. Moreover, a new amino acid substitution, T260M, within the pilin domain in one subspecies IIIb strain beneficial to binding to cells was highlighted in this study, even though the biofilm-forming and Caenorhabditis elegans-killing abilities exhibited no significant differences in variants. Combined with point mutations being a natural tendency due to positive selection in harsh environments, we speculate that allelic variation T260M probably contributes to pathoadaptive evolution in Salmonella enterica subspecies IIIb.